Analisis efektivitas kerja karyawan PT PLN (Persero) dipengaruhi oleh kedisiplinan kerja dan lingkungan kerja - Khumaeroh, Annisa Bella; Maulia, Indah Rizki (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This study aims to analyze the influence of work discipline and work environment on the effectiveness of PT PLN (Persero) employees. The research method used is a quantitative correlational method. The sample was selected using the incidental sampling technique with 100 employees as respondents. Data collection using a Likert scale questionnaire via Google Form. The analysis method used is the multiple statistical analysis method. The results of this study indicate that work discipline and work environment simultaneously have a positive and significant influence on work effectiveness. It can be concluded that if work discipline and work environment increase, work effectiveness will also increase.